2020
DOI: 10.1080/2162402x.2020.1776577
|View full text |Cite
|
Sign up to set email alerts
|

Modeling human pediatric and adult gliomas in immunocompetent mice through costimulatory blockade

Abstract: Currently, human glioma tumors are mostly modeled in immunodeficient recipients; however, lack of interactions with adaptive immune system is a serious flaw, particularly in the era when immunotherapies dominate treatment strategies. Our group was the first to successfully establish the orthotopic transplantation of human glioblastoma (GBM) in immunocompetent mice by inducing immunological tolerance using a short-term, systemic costimulation blockade strategy (CTLA-4-Ig and MR1). In this study, we further vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…High malignancy and recurrence rates make glioma the most lethal primary brain tumor of the central nervous system ( 35 , 36 ). With the development of glioma mechanism research and clinical treatment, some prognostic factors have been well-characterized, including WHO grade, isocitrate dehydrogenase (IDH) status, and 1p/19q codeletion status.…”
Section: Discussionmentioning
confidence: 99%
“…High malignancy and recurrence rates make glioma the most lethal primary brain tumor of the central nervous system ( 35 , 36 ). With the development of glioma mechanism research and clinical treatment, some prognostic factors have been well-characterized, including WHO grade, isocitrate dehydrogenase (IDH) status, and 1p/19q codeletion status.…”
Section: Discussionmentioning
confidence: 99%
“…As has been well described in the literature for the study of GBM in vivo [ 60 , 61 , 62 , 63 ], we suggest a xenograft approach of human tumor stem cell models in rodent carriers, ideally in immune-tolerant models [ 64 ], to investigate the immune relevance of the applied intervention using nanocarried-CB839 in the future. Such an immunocompetent mouse model for human GBM cells—which has also been recently used for testing additional disease types [ 65 ]—would also help to study the effects of Au-CB839 NPs on the immune microenvironment of the tumor. Given the emergence of immune therapies as effective cancer treatments, the inclusion of such assays in future drug development projects are desirable to increase translational relevance.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study revealed that DMT and psilocin down‐regulate CD80 co‐stimulatory molecule expression on the surface of microglial cells, with and without LPS stimulation (Kozlowska, Klimczak, Wiatr et al, 2021). The co‐stimulatory signal is crucial for recruiting adaptive immune cells; therefore, blockade of co‐stimulatory molecules an attractive immunosuppressive strategy (Lan et al, 2020). The unique properties of psychedelics in suppressing inflammatory responses (Szabo et al, 2014; Flanagan & Nichols, 2018; Nardai et al, 2020), and promoting neural survival (Szabo et al, 2016) and plasticity (Ly et al, 2018), could be a strong rationale for the hypothesis that psychedelics might support grafted cells and facilitate their survival for therapeutic benefits.…”
Section: Research Perspectives For Psychedelics In Preventing Neurode...mentioning
confidence: 99%
“…Our recent study revealed that DMT and psilocin down-regulate CD80 co-stimulatory molecule expression on the surface of microglial cells, with and without LPS stimulation (Kozlowska, Klimczak, Wiatr et al, 2021). The co-stimulatory signal is crucial for recruiting adaptive immune cells; therefore, blockade of co-stimulatory molecules an attractive immunosuppressive strategy (Lan et al, 2020).…”
Section: Prospect Implications For Regenerative Medicinementioning
confidence: 99%